Unimas majlis perwakilan pelajar (MPP) portal - Alvina, Pengiran.; Beatrice, Ak Kanang; Haroza, Bt Pandi; Lorna Munan, Bt Alexius Nayang. (Universiti Malaysia Sarawak (UNIMAS), 2003)
In this Internet era, many have realized the benefit of a portal. A portal is a gateway to access information by just a click of a mouse. Information and Communication Technology (lCT) has resulted in the development of portal in universities in Malaysia and also portal for Student Representative Council, which is known as Majlis Perwakilan Pelajar (MPP). With the portal for MPP, information are easier to be broadcasted and students can easily voice out their views and ideas. The development of this Majlis Perwakilan Pelajar Portal is one ofthe many portals that are upgrading the traditional way of broadcasting information to more technological and systematic way. This thesis is written based on the development of UNIMAS Majlis Perwakilan Pelajar (MPP) Portal.